2003
DOI: 10.1211/002235702694
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-dependent and -independent vasodilator effects of eugenol in the rat mesenteric vascular bed

Abstract: The possible involvement of the endothelium in the vasodilator action of eugenol was investigated in the mesenteric vascular bed (MVB) of the rat. Bolus injections of eugenol (0.2, 2 and 20 micromol) and acetylcholine (ACh; 10, 30 and 100 pmol) induced dose-dependent vasodilator responses in noradrenaline-precontracted beds that were partially inhibited by pretreatment of the MVB with deoxycholate (1 mg mL(-1)) to remove the endothelium (approximately 14% and approximately 30% of the control response remaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 29 publications
3
31
1
2
Order By: Relevance
“…Our data indicate that eugenol-induced relaxation in mesenteric arteries is mediated, in part, via the endothelium. These results agree with previous studies demonstrating that eugenol-induced vasorelaxation is partially dependent on the endothelium in rat aorta, a conduit vessel, and a whole mesentery preparation (Criddle et al, 2003;Damiani et al, 2003). Eugenol also relaxed endothelium-denuded arteries.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data indicate that eugenol-induced relaxation in mesenteric arteries is mediated, in part, via the endothelium. These results agree with previous studies demonstrating that eugenol-induced vasorelaxation is partially dependent on the endothelium in rat aorta, a conduit vessel, and a whole mesentery preparation (Criddle et al, 2003;Damiani et al, 2003). Eugenol also relaxed endothelium-denuded arteries.…”
Section: Discussionsupporting
confidence: 93%
“…Eugenol also relaxed rat aorta and an intact mesenteric bed. The effects were shown to be partially dependent on the endothelium, but their mechanisms of action were unclear (Criddle et al, 2003;Damiani et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study the relaxant action of anethole was also independent of nitric oxide production since it was not inhibited by L-NAME, a nitric oxide synthase blocker (Rees et al, 1989) suggesting a similar profile of action to eugenol. In agreement, we have previously shown that eugenol evoked vasodilation of perfused mesenteric resistance vessels that was partially endotheliumdependent, although apparently independent of nitric oxide, endothelium-derived hyperpolarizing factor or prostacyclin production (Criddle et al, 2003). In a similar manner, the effects of anethole on the rat isolated aorta were not inhibited by indomethacin, ruling out possible involvement of prostaglandins.…”
Section: Discussionsupporting
confidence: 89%
“…Its structural analogue eugenol (4-allyl-2-methoxyphenol), also a major constituent of medicinal plant essential oils, has been more extensively characterized in blood vessels. For example, we have previously demonstrated both endothelium-dependent and -independent vasodilator effects of eugenol in rat perfused mesenteric Life Sciences 81 (2007) 1085 -1093 www.elsevier.com/locate/lifescie resistance arteries (Criddle et al, 2003), whilst contractile studies in isolated blood vessels have indicated a modulatory effect of the endothelium on eugenol-induced vasorelaxation (Nishijima et al, 1998;Damiani et al, 2003). Therefore the aim of the present study was to compare the actions of anethole and its isomer estragole, with those of eugenol and isoeugenol (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…BM-derived DC were generated from primary cultures of femoral marrow from 6-to 8-wk-old female wild-type (WT) and IL-6 Ϫ/Ϫ mice as described previously (18). In brief, BM cells were flushed from the femurs of 6-to 8-wk-old mice using an RPMI 1640-filled syringe to obtain a single-cell suspension.…”
Section: In Vitro Differentiation Of DC From Bm Precursorsmentioning
confidence: 99%